Enhancing the effectiveness of evaluation in public sector performance in Vietnam - Tran Thanh Nga (Journal of State Management, 2025)
The operational efficiency of public bodies is a crucial element in improving the quality of public governance and administrative services. However, the current evaluation practices in Vietnam are facing significant challenges, primarily due to the absence of a comprehensive system of criteria and measurement methods. To address this, it is essential to research, develop, and implement a set of comprehensive evaluation criteria. These criteria will be instrumental in enhancing the effectiveness of public bodies across various aspects, including operational efficiency, human resource quality, achieved outcomes, impact assessment, and public service quality. This paper proposes a series of recommendations to improve the evaluation criteria system, thereby enhancing the quality of state management and promoting the sustainable development of public administration in Vietnam.